THE DYNAMICS OF CHARACTER ASSASSINATION THROUGH CYBERBULLYING ON TWITTER - Mucklis; Feni Khairifa (Academic Solution Publisher, 2025)
This study explores the dynamics of character assassination through cyberbullying on Twitter as an increasingly prominent social phenomenon in the digital era. As social media becomes a central space for public communication, individual reputations can be rapidly constructed or damaged. Character assassination on social media constitutes a form of digital violence that poses serious risks to victims’ psychological well-being and social standing. Employing a qualitative approach, this research analyzes patterns of attacks, perpetrators’ motivations, and victims’ experiences through content analysis of tweets and in-depth interviews with individuals affected by cyberbullying. The findings indicate that cyberbullying on platform X is reinforced by key features of a network society, including anonymity, rapid information circulation, and global visibility. These factors intensify psychological harm such as stress and depression, while also undermining victims’ social reputation and digital identity. Additionally, platform algorithms may unintentionally amplify negative content by prioritizing highly engaging posts. Addressing this issue requires collaborative efforts among social media platforms, government institutions, and communities through improved moderation systems, effective reporting mechanisms, and victim support services.